Formulation and Optimization of Avocado Oil (Persea americana oil) Emulsion as a Carrier for Vitamin E (α-Tocopherol) with Sun Protection Factor Analysis in Lotion Preparation - Laela Nur' Aini; Enggar Sulistyo Wibisono; Vita Paramita; Indah Hartati (Journal of Vocational Studies on Applied Research, 2026)
This study aims to formulate and optimize an emulsion based on avocado oil (Persea americana oil) as a delivery system for vitamin E (α-tocopherol) in cream lotion preparations using the Response Surface Methodology (RSM). Avocado oil was chosen due to its high α-tocopherol content and skin benefits. Optimization was carried out by varying the stirring time, homogenization speed, and avocado oil–Tween 80 ratio. The resulting emulsion was evaluated for vitamin E content, Sun Protection Factor (SPF), viscosity, pH, density, and physical stability. The optimal formulation was achieved at 11.9 min of stirring, 1000 rpm speed, and a ratio of 0.4798, resulting in a vitamin E content of 0.0913% and an SPF value of 14.02. The results showed that the oil–Tween 80 ratio had a significant effect on SPF value, while stirring speed had a low effect on vitamin E content. This emulsion shows potential as an effective topical antioxidant and UV protection formulation.